Antioxidant and antimicrobial activities of methanol leaf extract of Aegle Tamilnadensis Abdul Kader - M Chella Kumar; S Abdul Kader; C Sivaraj; N Raaman (International Journal of Phytomedicine, 2017)
The present investigation was aimed to evaluate the phytochemical constituents, free radical scavenging activities, antioxidant properties and antimicrobial activities of the methanol leaf extract of Aegle tamilnadensis Abdul Kader. The phytochemicals present in the methanol leaf extract of A. tamilnadensis Abdul Kader were determined qualitatively and quantitatively using standard procedures. The antioxidant activities were carried out by DPPH free radical scavenging assay, OH• radical scavenging assay, NO• radical scavenging assay, Fe3+ reducing power assay, and phosphomolybdenum reduction assay methods. The antimicrobial activity was carried out by well diffusion method. The methanol leaf extract of A. tamilnadensis Abdul Kader showed good free radical scavenging as well as reducing power activities which were found to increase with the increasing concentration of the extract. The study revealed the presence of major phytochemicals such as phenols and flavonoids at the concentration of 211.0 mg/g at 100 µg and 52.91 mg/g at 100µg/mL respectively. The present study revealed that the methanol leaf extract of A. tamilnadensis Abdul Kader possess significant antioxidant and antimicrobial activities.